Estuarine sedimentation - Khan, Ashraf Hossain; Suphat Vongvisessomjai; Nishimura, Hitoshi; Prida Thimakorn; Government of Switzerland (Bangkok : Asian Institute of Technology, 1975)
Most of the famous ports of the world are located in estuaries. Costs of dredging to maintain the navigation channel are high as the magnitude of the oscillatory current in the estuaties, predominated by tidal action, are not so strong which favour the sedimentation process. Availabl e data of eight estuaries are analyzed to yield some families of curve using appropriate dimensionless parameters. The relationship between tide, streamflow, and distance from river mouth is obtained for the Chao Phya Estuary to predict the tidal fluctuation at various distance. Suspended load and rate of sedimentation in the dimensionless forms Qss , Qsb Qf Qf showed good correlation when related to the volume ratio of tidal prism to fresh water discharge, i.e. 2P1/T , 2P2/T Qf Of and estuary number E1 and E2 . Location of shoaling in the dimensionless form Ls or Ls H 3/Ps showed good correlation when related to estuary number E2 {u2022} 2 The results are useful in estimating the needed data in planning the development of other estuaries.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Estuarine sediments